MEDIATION OF HOUSEHOLD CONFLICT IN THE KUA PAHANDUT PALANGKA RAYA - Vichi Novalia; Sadiani; Sabarudin Ahmad (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to examine the resolution of domestic conflicts as an important alternative in reducing the divorce rate through non-litigation carried out by officers of the Office of Religious Affairs (KUA) in an effort to reconcile the disharmony of households in society. The focus of the research problem is 2 things: 1) How is the practice of mediation in resolving domestic conflicts in the KUA of Pahandut District, Palangka Raya City?, and How is the effectiveness of resolving domestic conflicts in the KUA of Pahandut District, Palangka Raya City?. The research method used is juridical-empirical with a socio-legal approach through analysis of laws and regulations, Islamic legal concepts, and empirical data obtained from interviews, observations, and documentation at the KUA of Pahandut District. The results of the study show; 1) The practice of mediation in resolving domestic conflicts in the KUA of Pahandut District, Palangka Raya has a strategic role in resolving non-litigation conflicts, because it is preventive and has Islamic values, with the concept of iṣlāḥ . In the implementation of mediation, it is carried out through deliberation and providing advice with a persuasive approach to the disputing husband and wife so that it can be resolved openly with good intentions so that peace and harmony can be achieved again. 2) The effectiveness of resolving household conflicts at the KUA Pahandut District Palangka Raya is still hampered by high emotions, the involvement of third parties, weak commitment to reconciliation, and limited authority and resources of mediators to reconcile disputing couples, so it is necessary to strengthen the capacity of mediators, optimize the role of BP4 to participate in mediator training as an important step to strengthen the mediation function of the Office of Religious Affairs as an instrument for preventing divorce in line with the objectives of Islamic family law.